2017
DOI: 10.1017/jfm.2017.577
|View full text |Cite
|
Sign up to set email alerts
|

The impact of static and dynamic roughness elements on flow separation

Abstract: The use of static or dynamic roughness elements has been shown in the past to delay the separation of a laminar boundary layer from a solid surface. Here, we examine analytically the effect of such elements on the local and breakaway separation points, corresponding respectively to the position of zero skin friction and presence of a singularity in the roughness region, for flow over a hump embedded within the boundary layer. Two types of roughness elements are studied: the first is small and placed near the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…An isolated three-dimensional surface-mounted obstacle, in the form of a sufficiently high slender hump, is an effective means to force reattachment of an oncoming two-dimensional marginally separating boundary layer. Servini, Smith & Rothmayer (2017, 2018) studied the impact of a two-dimensional dynamic roughness element on a separating boundary layer. Recently, Karp & Hack (2020) showed, by numerical simulations, reduction of separation bubble size by the so-called optimal disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…An isolated three-dimensional surface-mounted obstacle, in the form of a sufficiently high slender hump, is an effective means to force reattachment of an oncoming two-dimensional marginally separating boundary layer. Servini, Smith & Rothmayer (2017, 2018) studied the impact of a two-dimensional dynamic roughness element on a separating boundary layer. Recently, Karp & Hack (2020) showed, by numerical simulations, reduction of separation bubble size by the so-called optimal disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…in a manner similar to that carried out in Servini et al (2017). The dynamic roughness function itself can be written as…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…When the fracture roughness was increased, the eddy volumes were increased, but the effective hydraulic conductivities were decreased, even though the Re values remained the same [8]. Servini et al [9] investigated the impact of static and dynamic roughness elements on the flow separation process. They found that both types of roughness can have an effect.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers examined two distinct sizes and shapes of roughness elements. The first roughness element is relatively small and is located close to the point of vanishing skin friction, and the second roughness element is significantly larger and extends downstream [9]. Prasad et al [5] conducted a study on the effect of river discharges controlled by a dam and tidal currents on the salt wedge intrusion in the Godavari River estuary on the east coast of India.…”
Section: Introductionmentioning
confidence: 99%